Dinamika Kolaborasi dalam Penanganan Pemberangkatan Pekerja Migran Nonprosedural di Kabupaten Ende, Provinsi Nusa Tenggara Timur - Helenerius Ajo Leda; Dominikus Rangga Hayon (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study analyses collaborative dynamics and identifies structural barriers in the governance of the management of illegal labour migration in Ende Regency, using a Collaborative Governance framework that encompasses principal engagement, shared motivation, and capacity for joint action. The research method employed is a descriptive qualitative approach. Data were collected through in-depth interviews with key actors (local government, BP3MI, the police, NGOs, and religious organisations), document analysis, policy archives, and a review of relevant publications. Data were analysed thematically through the stages of organisation, comprehensive reading, coding, theme identification, and interpretation, referencing the Collaborative Governance Regime framework. The research findings indicate that collaboration among actors remains at an ‘emerging’ stage, characterised by partial engagement, weak shared motivation, and limited institutional capacity. The government’s role tends to be administrative, whilst non-state actors play a more substantive role. Key obstacles include the absence of local regulations, weak coordination, and a lack of resources. Strengthening regulations, coordination systems, and collaborative learning is necessary to achieve more effective migration governance.